2002
DOI: 10.1203/00006450-200202000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Rat Postnatal Lung Alveolar Development by Glucocorticoids: Involvement of the p21CIP1 and p27KIP1 Cyclin-Dependent Kinase Inhibitors

Abstract: It has been shown that glucocorticoids accelerate lung development by limiting alveolar formation resulting from a premature maturation of the alveolar septa. Based on these data, the aim of the present work was to analyze the influence of dexamethasone on cell cycle control mechanisms during postnatal lung development. Cell proliferation is regulated by a network of signaling pathways that converge to the key regulator of cell cycle machinery: the cyclin-dependent kinase (CDK) system. The activity of the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Glucocorticoids have previously been shown to regulate protein levels of both CKIs in isolated and cultured lung epithelium. Dexamethasone treatment induced p21 CIP1 protein levels in early postnatal lung and lung cancer cell lines (Corroyer et al 2002; Greenberg et al 2002) and a glucocorticoid responsive region has been characterized in the promoter region of the p21 CIP1 gene (Cha et al 1998). Similarly, dexamethasone increased p57 KIP2 mRNA levels in human bronchial epithelial cells (Puddicombe et al 2003) and a functional GRE has been described in the promoter region of the human p57 KIP2 gene (Alheim et al 2003), Interestingly, another report has shown an increase of protein, but not increased mRNA levels of p21 CIP1 in cultured neonatal type II AECs following dexamethasone treatment (Corroyer et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids have previously been shown to regulate protein levels of both CKIs in isolated and cultured lung epithelium. Dexamethasone treatment induced p21 CIP1 protein levels in early postnatal lung and lung cancer cell lines (Corroyer et al 2002; Greenberg et al 2002) and a glucocorticoid responsive region has been characterized in the promoter region of the p21 CIP1 gene (Cha et al 1998). Similarly, dexamethasone increased p57 KIP2 mRNA levels in human bronchial epithelial cells (Puddicombe et al 2003) and a functional GRE has been described in the promoter region of the human p57 KIP2 gene (Alheim et al 2003), Interestingly, another report has shown an increase of protein, but not increased mRNA levels of p21 CIP1 in cultured neonatal type II AECs following dexamethasone treatment (Corroyer et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1. In the study of Corroyer et al (24), newborn rats were given a 4-d treatment with DEX (0.1-0.01 g/g body weight DEX sodium phosphate daily on d 1-4), or saline. There was no significant difference between the male and female sets (p Ͼ 0.05); however, the male and female sets were analyzed separately and it was found that there were significant differences among the sets within the female and male groups (p Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The animals used were part of our studies about the pulmonary effects of a neonatal high-dose short-term glucocorticoid treatment of rats (11,22,29,30,34,42). In addition, the controls of this experiments were used in other studies analyzing lung development (14 -16, 27, 33, 43).…”
Section: Methodsmentioning
confidence: 99%